(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The relevance of the work lies in the fact that physical culture and sports serve as an important means of preserving and strengthening human health. The importance of physical culture and sports in the multifaceted process of educating a person, developing his physical qualities, strengthening health, and increasing efficiency is undeniable